Identification of a Novel Plasmid Lineage Associated With the Dissemination of Metallo-β-Lactamase Genes Among Pseudomonads - Di Pilato, Vincenzo; Antonelli, Alberto; Giani, Tommaso; Henrici De Angelis, Lucia; Rossolini, Gian Maria; Pollini, Simona (Frontiers in Microbiology, 2019)
Acquisition of metallo-β-lactamases (MBLs) represents one of most relevant resistance mechanisms to all β-lactams, including carbapenems, ceftolozane and available β-lactamase inhibitors, in Pseudomonas spp. VIM-type enzymes are the most common acquired MBLs in Pseudomonas aeruginosa and, to a lesser extent, in other Pseudomonas species. Little is known about the acquisition dynamics of these determinants, that are usually carried on integrons embedded into chromosomal mobile genetic elements. To date, few MBL-encoding plasmids have been described in Pseudomonas spp., and their diversity and role in the dissemination of these MBLs remains largely unknown. Here we report on the genetic features of the VIM-1-encoding plasmid pMOS94 from P. mosselii AM/94, the earliest known VIM-1-producing strain, and of related elements involved in dissemination of MBL. Results of plasmid DNA sequencing showed that pMOS94 had a modular organization, consisting of backbone modules associated with replication, transfer and antibiotic resistance. Plasmid pMOS94, although not typable according to the PBRT scheme, was classifiable either in MOBF11 or MPFT plasmid families. The resistance region included the class I integron In70, carrying blaVIM-1, in turn embedded in a defective Tn402-like transposon. Comparison with pMOS94-like elements led to the identification of a defined plasmid lineage circulating in different Pseudomonas spp. of clinical and environmental origin and spreading different MBL-encoding genes, including blaIMP-63, blaBIM and blaVIM-type determinants. Genetic analysis revealed that this plasmid lineage likely shared a common ancestor and had evolved through the acquisition and recombination of different mobile elements, including the MBL-encoding transposons. Our findings provide new insights about the genetic diversity of MBL-encoding plasmids circulating among Pseudomonas spp., potentially useful for molecular epidemiology purposes, and revealed the existence and persistence of a successful plasmid lineage over a wide spatio-temporal interval, spanning over five different countries among two continents and over 20-years.